Provocação para um resgate na construção das relações literárias Brasil/Alemanha - Barbosa, Fábio Luís Chiqueto [UNESP] (My University, 2011)
The present article starts from the initial consideration that, in the perspective of the investigations of the Brazil/Germany literary relations, not always the study of the presence of Brazilian literary works in Germany has been receiving sufficient attention in Brazil. Initially, the natural existence of mental paths is signalized. This fact, in a way, guides the general lines of the critical Brazilian thought in the consideration of aspects of the cultural and literary dialog here in question. This consideration favors the movement that goes from Germany to Brazil, which doesn’t give enough space for the study of the opposite movement. Finally, some historical literary elements are presented, which can base deeper studies of the literary relations Brazil/Germany in the sense that here is intended to be rescued, i.e., the one that goes from South America to Europe.

O presente artigo parte da premissa inicial que, na perspectiva das investigações das relações literárias entre o Brasil e a Alemanha, nem sempre o estudo da presença de produções literárias brasileiras na Alemanha tem recebido atenção suficiente no Brasil. Assinala-se, em princípio, a existência natural de corredores de pensamento os quais, em certa medida, orientam as linhas gerais do pensamento crítico brasileiro na consideração de aspectos que privilegiam o diálogo cultural e literário em questão no movimento que vai da Alemanha ao Brasil, o que deixa pouco espaço para o estudo do movimento contrário. Em seguida, procede-se à apresentação de alguns elementos histórico-literários que podem subsidiar um trabalho mais amplo e profundo do estudo das relações literárias Brasil/Alemanha no sentido que aqui se pretende resgatar, isto é, aquele que vai do primeiro para o segundo.
Keywords: Literature response; Brazilian Literature; German Literature Syste; Recepção literária; Literatura Brasileira; Sistema Literário Alemão